PENYEDIAAN PANGAN YANG AMAN DAN BERKELANJUTAN GUNA MENDUKUNG TERCAPAINYA KETAHANAN PANGAN - Hanafie, Rita (Jurnal Sosial Ekonomi Pertanian, 2010)
With going concern organic agriculture, not even produce the peaceful food can be yielded because minim of usage of chemical materials, however on a long term ability agroecosistem a a whole defensible also so that produce and agriculture productivity can is always improved. Ready of settled domestic product and have continuation expected can push the agricultural produce price stability so that impecunious society group and farmer can reach the food though its purchasing power relative lower. With security and continue the food consumption and production, expected by the food quality consumption of the society in general can mount so that society can live healthyly, productive and active to fill, to continue and improve the development.Kata kunci: pangan aman berkelanjutan, ketahanan pangan